Umbilical cord mesenchymal stem cells and their secretome: a new frontier in orthopedic medicine - Tito Sumarwoto; Romaniyanto; Sholahuddin Rhamtomy; Mujaddid Idulhaq; Asep Santoso (Universa Medicina, 2026)
Umbilical cord mesenchymal stem cells (UC-MSCs) have gained significant attention in regenerative medicine due to their unique biological properties, including high proliferation capacity, low immunogenicity, and potent immunomodulatory effects. These characteristics make UC-MSCs particularly promising for orthopedic applications, where the repair and regeneration of musculoskeletal tissues such as bone, cartilage, tendons, ligaments, and nerves are critical for restoring function. The secretome of UC-MSCs—comprising bioactive molecules such as exosomes, cytokines, and growth factors—offers a powerful, cell-free therapeutic option through paracrine signaling, further enhancing their therapeutic potential. A literature search was conducted in major databases (PubMed, ScienceDirect, SpringerLink, Google Scholar) for English articles from 2010–2025 using keywords related to UC‑MSCs and orthopedic regeneration. This review explores the role of UC-MSCs and their secretome in orthopedic tissue repair, focusing on their application in bone healing, cartilage regeneration, tendon-ligament repair, and nerve regeneration with their innovative delivery. Despite the promising potential of UC-MSC therapies, several challenges remain, including regulatory hurdles, long-term safety concerns, and the scalability of cell-based and secretome-based therapies for widespread clinical use. Although umbilical cord MSCs are not yet widely applied in clinical practice, increasing evidence suggests that they offer significant therapeutic potential, especially in the treatment of autoimmune and neurodegenerative diseases. The UC-MSCs and their secretome represent a transformative approach in orthopedics, offering new avenues for treating complex musculoskeletal injuries and degenerative diseases. Ongoing advancements in this field will likely unlock their full potential, making them viable options for clinical use in the near future.